SOCIALIZATION OF HIGH-FIBER AND HIGH-PROTEIN MENUS FOR INDIVIDUALS WITH TYPE 2 DIABETES MELLITUS - Suzan, Raihanah; Halim, Rita; Amalia, Fenny; Ayudia, Esa Indah; Puspasari, Anggelia; Gading, Patrick Wiliam (Medical Dedication (medic) : Jurnal Pengabdian kepada Masyarakat FKIK UNJA, 2025)
ABSTRACT Type 2 Diabetes Mellitus (T2DM) is a chronic disease prevalent worldwide and is one of the biggest public health challenges of the 21st century. Lifestyle changes and proper dietary patterns have proven effective for the prevention and management of diabetes mellitus. Emerging evidence shows that a high-protein and high-fiber diet is particularly beneficial. This Community Service Activity was conducted at the Puskesmas Koni in Jambi City. Participants attended a session on high-fiber and high-protein menu guidelines for individuals with T2DM presentation. The activity was attended by 30 participants, comprising 19 volunteers and 11 individuals with T2DM. Most participants, 21 people (70%) were aged 19 to 59 years, and 18 participants (60%) were female. The average pre-test score was 49.7, and the post-test score was 75. There was an increase in participants' knowledge after the socialization of the high-fiber and high-protein menu guidelines for individuals with T2DM. Keywords: High-Protein Diet; High-Fiber Diet; Menu Guidelines; T2DM; Blood Sugar Management